Women's perspectives on the management and consequences of hyperemesis gravidarum - a descriptive interview study - Gro C. Havnen; Maria Bich-Thuy Truong; Mai-Linh H. Do; Kristine Heitmann; Lone Holst; Hedvig Nordeng (Taylor & Francis Group, 2019)
Objective: Hyperemesis gravidarum (HG) affects 0.3-3% of pregnant women and is a leading cause of hospitalization in early pregnancy. The aim of the study was to investigate women's treatment and management of HG, as well as the consequences of HG on women's daily life. Design and setting: A cross-sectional study based on a structured telephone interview and an online questionnaire. Participants were recruited by social media and by the Norwegian patient's organization for HG. Subjects: Norwegian women that experienced HG. Main outcome measure: Women's perspectives on management and consequences of HG. Results: The study included 107 women. Maternal morbidity was profound; about 3/4 of participants were hospitalized due to HG, and the majority showed clinical signs of dehydration (79%), ketonuria (75%), and >5% weight loss (84%). Antiemetics were used by >90% and frequently prescribed "as needed". Metoclopramide (71%) and meclozine (51%) were most commonly used. Participants described HG as having severe psychosocial consequences and profound impact on daily activities. Almost two out of five reported thoughts of elective abortion, and 8 women had at least one elective pregnancy termination due to HG. Overall, 20 women (19%) changed GPs due to dissatisfaction with HG management. Conclusion: Despite the high psychosocial burden and major impact on daily activities, many women with HG reported a lack of support from healthcare professionals and suboptimal management. Greater awareness and knowledge among healthcare professionals is needed to improve care for women with HG.Key Points There is a paucity of studies on management and the consequences of HG on women's daily lives and psychosocial burden. We found that: • Many women described HG as one of their worst life experiences with profound morbidity. • Many women reported suboptimal management of HG and lack of support from healthcare professionals. • Greater understanding of patient perspectives among healthcare professionals is important to improve care and management for HG patients.